Витрати підприємства, їх значення та вплив на ефективність роботи підприємства - Фізлова, Л.Д.; Харченко, В.О. (Культура народов Причерноморья, 2013)
У цій статті розглянуто сутність поняття «витрати» з точки зору вітчизняних і
зарубіжних учених. Також розглянута класифікація витрат і фактори, що впливають на них.
Розглянуто формування витрат на прикладі підприємства харчової промисловості та вплив
операційних витрат на ефективність роботи підприємства. Для поліпшення ефективності діяльності
предпряития і оптимізації витрат було запропоновано використовувати аутсорсинг - як один і
потулярных методів оптимізації витрат в сучасних умовах.
Ключові слова: витрати, підприємство, виробництво, прибуток, аутсорсинг. В данной статье рассмотрена сущность понятия «расходы» с точки зрения
отечественных и зарубежных ученых. Также рассмотрена классификация расходов и факторы,
влияющие на них. Рассмотрено формирование расходов на примере предприятия пищевой
промышленности и их влияние на эффективность работы предприятия. Для улучшения эффективности
деятельности предпряития и оптимизации расходов было предложено использовать аутсорсинг - как
один и потулярных методов оптимизации расходов в современных условиях.
Ключевые слова: расходы, предприятие, производство, прибыль, аутсорсинг. This article discusses the essence of the concept of «expenses» from the point of view of domestic and
foreign scientists. Also we consider the classification of c expenses and factors affecting expenses of the
enterprise. We have considered the formation of the expenditure on the example of the enterprises of the food
industry. In the process of reviewing the structure of expenditures of the enterprise was detected that the
operating expenses accounted for the largest part of the expenses of the enterprise and directly affect the volume
of output of products, which renders a positive influence on the efficiency of the activities of the enterprise as a
whole. At the enterprise occupies the largest part of the material costs among the operating expenses. The
indicators of the formation the efficiency of expenses from operating activities were considered. When we have
considered the company's operating expenses, it was discovered that they were formed ineffective, as the costs of
the enterprise have increased, and the volume of production and financial results of the company decreased
significantly. For increase of efficiency of activity of the enterprise have been proposed activities for the
optimization of the expenditures of the enterprise. As one of the most popular methods of optimization of
expenses of the enterprise in modern conditions it was suggested to use outsourcing. Applying the outsourcing
company can considerably reduce expenses.
Key words: expenses, the enterprise, production, profit, outsourcing.